Iron deficiency anaemia. Issue 10021 (27th February 2016) - Lopez, Anthony; Cacoub, Patrice; Macdougall, Iain C; Peyrin-Biroulet, Laurent
Summary: Anaemia affects roughly a third of the world's population; half the cases are due to iron deficiency. It is a major and global public health problem that affects maternal and child mortality, physical performance, and referral to health-care professionals. Children aged 0–5 years, women of childbearing age, and pregnant women are particularly at risk. Several chronic diseases are frequently associated with iron deficiency anaemia—notably chronic kidney disease, chronic heart failure, cancer, and inflammatory bowel disease. Measurement of serum ferritin, transferrin saturation, serum soluble transferrin receptors, and the serum soluble transferrin receptors–ferritin index are more accurate than classic red cell indices in the diagnosis of iron deficiency anaemia. In addition to the search for and treatment of the cause of iron deficiency, treatment strategies encompass prevention, including food fortification and iron supplementation. Oral iron is usually recommended as first-line therapy, but the most recent intravenous iron formulations, which have been available for nearly a decade, seem to replenish iron stores safely and effectively. Hepcidin has a key role in iron homoeostasis and could be a future diagnostic and therapeutic target. In this Seminar, we discuss the clinical presentation, epidemiology, pathophysiology, diagnosis, and acute management of iron deficiency anaemia, and outstanding research questions for treatment.